2018
DOI: 10.3747/co.25.3750
|View full text |Cite
|
Sign up to set email alerts
|

Current Landscape of Immunotherapy for the Treatment of Metastatic Non-Small-Cell Lung Cancer

Abstract: For patients with advanced non-small-cell lung cancer (nsclc) lacking a targetable molecular driver, the mainstay of treatment has been cytotoxic chemotherapy. The survival benefit of chemotherapy in this setting is modest and comes with the potential for significant toxicity. The introduction of immunotherapeutic agents targeting the programmed cell death 1 protein (PD-1) and the programmed cell death ligand 1 (PD-L1) has drastically changed the treatment paradigms for these patients. Three agents-atezolizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…The Dako platform (Agilent Technologies/Dako, Carpinteria, CA, USA) has developed the 22C3 and 28‐8 antibodies in conjunction with pembrolizumab and nivolumab. The Ventana platform (Ventana Medical Systems Inc, Tucson, Arizona) has developed the SP142 and SP263 antibodies in conjunction with atezolizumab and durvalumab . Several clinical trials have demonstrated great heterogeneity in the cutoff levels and methods used for PD‐L1 testing and the assessment of PD‐L1 positivity based on the various assays …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dako platform (Agilent Technologies/Dako, Carpinteria, CA, USA) has developed the 22C3 and 28‐8 antibodies in conjunction with pembrolizumab and nivolumab. The Ventana platform (Ventana Medical Systems Inc, Tucson, Arizona) has developed the SP142 and SP263 antibodies in conjunction with atezolizumab and durvalumab . Several clinical trials have demonstrated great heterogeneity in the cutoff levels and methods used for PD‐L1 testing and the assessment of PD‐L1 positivity based on the various assays …”
Section: Introductionmentioning
confidence: 99%
“…The Ventana platform (Ventana Medical Systems Inc, Tucson, Arizona) has developed the SP142 and SP263 antibodies in conjunction with atezolizumab and durvalumab. 15,16 Several clinical trials have demonstrated great heterogeneity in the cutoff levels and methods used for PD-L1 testing and the assessment of PD-L1 positivity based on the various assays. 16,17 In patients with lung cancer, pathologists are increasingly facing the challenge of performing more molecular tests on smaller biopsy specimens generally obtained from minimally invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the most general occasion of cancer‐related death worldwide and is probably attributable to early metastasis . An understanding of the mechanism(s) driving metastatic cellular activity is vital for helping to reduce lung cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The 5 year overall survival data of the Keynote 001 trial, presented at the American Society for Clinical Oncology (ASCO) 2019 conference, revealed durable long-term responses to immune-checkpoint inhibition (ICPI), and an unprecedented 5-year OS of 13.4-29.6% (4)(5)(6). This is a drastic improvement over pre-ICPI 5 year survival rates, which were below 5% (7).…”
Section: Introductionmentioning
confidence: 99%